Tetrathiotetracene thin film morphology and electrical properties - Pudzs, K.; Vembris, A.; Busenbergs, J.; Rutkis, M.; Woodward, Simon (Elsevier, 2015)
The electrical properties of organic thin films are determined by their chemical constituents and the morphology of the films deposited. In this paper the morphology of vacuum sublimed (7∙10-6 mbar) tetrathiotetracene (TTT) thin films is shown to be strongly affected by the thermal deposition temperature (222-350 K) and rate of deposition. Mostly needle-like morphologies are identified by scanning electron microscopy. Optimal TTT purity (a pre-requisite for device preparation via subsequent oxidation) is evidenced by their initially low electrical conductivity. Altering the TTT morphology, by variation of the evaporation parameters, strongly affects this base electrical conductivity. Four probe conductivity measurements and charge extraction by linear increasing voltage methods are used to characterize film electrical properties. In-plane conductivity of up to 7.03∙10-5 S/cm is achieved for pure TTT thin films. Subsequent aerial oxidation resulted in a 3.4-fold increase in electrical conductivity.